Peran Gereja dalam Mewujudkan Tanggung Jawab Budaya Manusia dan Pelestarian Lingkungan Hidup - Waruwu, Anwar Three Millenium; Erastus, Stephanie; Zebua, Yabes Yohanes (TEVUNAH: Jurnal Teologi dan Pendidikan Kristen, 2024)
The purpose of this study is to elucidate the nature of human responsibility within cultural contexts, focusing on the role of the Church in upholding and applying moral values reflected in the cultural mandate of humanity. The research methodology employed is a qualitative approach through a literature review coupled with an in-depth analysis of relevant theories. Findings indicate that the Church plays a crucial role in promoting human cultural responsibility and environmental conservation, not merely as a place of worship but also as a moral and ethical guide for its congregation. The Church must design educational and service programs that foster cultural and environmental missions and actively participate in environmental conservation efforts and moral character formation. This study contributes novel insights into understanding the Church's responsibility within social and ecological contexts, encompassing spiritual dimensions and humanitarian and environmental aspects.